Analisa dan Perancangan Sistem Pencatatan Pendapatan Berbasis Website dengan Menggunakan Metode Waterfall untuk Meningkatkan Kinerja Bisnis pada Cafe Kitorato (PT Kita Setara Indonesia) - Amirulah Kaharudin; Ari Agus Supriyadi; Muhlis; Saprudin (CV. Multi Kreasi Media, 2023)
Cafe Kitorato is a cafe business aimed at providing customers with a unique culinary experience. However, a common problem that occurs is the lack of efficiency in income recording and data management, which can have a negative impact on the overall performance of the business. Therefore, this research aims to analyze and design a web-based income recording system using the Waterfall method, with the hope of improving the performance of Cafe Kitorato. The research begins with an in-depth analysis of Cafe Kitorato's business needs and requirements in terms of income recording. The Waterfall method is chosen as the approach for structured and well-documented system development. The stages in the Waterfall method, namely requirement analysis, system design, implementation, testing, and maintenance, are followed systematically. In the requirement analysis phase, the data needed for cafe income recording is collected and analyzed. Next, the system design is carried out by designing an intuitive and user-friendly website interface to facilitate its usage by cafe staff. The system is implemented by building a website capable of real-time income recording and generating accurate financial reports. The test results show that the web-based income recording system using the Waterfall method has been successfully implemented at Cafe Kitorato. The use of this system helps expedite the income recording process, reduce human errors, and improve data accuracy. In field testing, the system successfully generated faster financial reports that can be accessed online by cafe management.in conclusion, the use of a web-based income recording system with the Waterfall method can enhance the business performance at Cafe Kitorato. This system helps improve efficiency in income recording and data management, which, in turn, has a positive impact on business decision-making. This research provides an important contribution to the development of information systems to enhance business performance in the culinary industry, particularly in the cafe business.